International Volunteering Capacity Development: Volunteer Partner Organization Experiences of Mitigating Factors for Effective Practice. Issue 2 (4th May 2019) - Tiessen, Rebecca; Lough, Benjamin J.
Abstract: Scholarly studies documenting the relationship between international volunteering and capacity development for international development organizations have increasingly presented the benefits and challenges of international volunteering from the perspective of partner organizations, thereby filling an important gap in the scholarship on international volunteering. As this body of literature grows, we can identify common themes pertaining to capacity development outcomes for international development organizations in the Global South. We examine the emergent body of literature on insights provided by host country volunteer partner organizations (VPOs) in relation to international volunteering outcomes, particularly as they relate to the positive and negative contributions to capacity development. Building on this scholarship, the paper builds on the studies documenting benefits and challenges of hosting international volunteers by uncovering diverse experiences of partner organizations that participate in a range of international volunteer program models (e.g. duration of volunteer service; working with a team of local volunteers; volunteer skills and competencies; language and technical training requirements, etc.). The empirical study presented in this paper involved cross-national, multivariate analyses of diverse experiences of partner organizations, drawing on findings from 288 survey responses by VPO staff from 68 countries. The findings from this study advance the scholarship on agency, subaltern voices and VPO experiences by documenting mitigating factors that contribute to a more in-depth understanding of capacity development contributions of international volunteers.